Designing an Android Application for Electronic Recruitment within Institutions in Libya using the FireBase Database - bin Taher, Nada Ibrahim; Abu Dhaina, Asmaa; Abu Rahhouma , Fatima Rahouma (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Today, the world is witnessing a huge development in technology and technical developments, the most prominent of which was smart phones and their applications, which greatly improved the field of employment and helped meet the needs of its beneficiaries, and contributed to solving many problems, the most important of which is the difficulty of obtaining sufficient information about jobs in traditional employment, and restricting the application for jobs to a specific time and place and wasting a lot of time for the job seeker, and the research is summarized in creating an Android application under the name Hire Me, whose purpose is to provide and design an application that helps to achieve the electronic recruitment process and provide an electronic means of communication for job seekers and choose the required job. The selection of qualified manpower and the competencies needed by any institution in a standard circumstance, and due to the clarity of the system requirements, the Waterfall Model methodology was used as an implementation model for the application, and the necessary data was collected from electronic and traditional sources, as well as general research was used in various sources of information, and it was used. The experimental approach to analyze the system and use the Unified Modeling Language (UML) in it, and to design the system, the Android Studio program was used to build the application using both JAVA and XML languages. This application was linked to a database (Firebase), and finally the partial and complete testing was done to detect and handle errors, and it was proven. The results of this research are that all the desired goals have been achieved, and an easy-to-use system free of complexity has been reached.